Internationalization at home: internationalizing the university experience of staff and students - Robson, Sue (Educação, 2017)
Internationalization has become a key strategic priority of many universities around the world. It is frequently regarded as a means to enhance the quality of higher education through strategic partnerships, collaborative research and teaching initiatives, for knowledge exchange and creation. Higher education internationalization often focuses primarily on the mobility of both staff and students as a means to improve their international outlook and intercultural capabilities. However, this paper argues that if universities are to become truly ‘international’, they should start ‘at home’. It considers how a review of current internationalization practices, involving educators, students, staff development and professional service units, and those in leadership positions, can help higher education institutions to move towards a more values-based and ethical approach to internationaliza ***Internacionalização em casa: internacionalização da experiência universitária de funcionários e estudantes*** A internacionalização tornou-se prioridade estratégica para muitas universidades ao redor do mundo. É comumente considerada uma forma de ampliar a qualidade da Educação Superior, através de parcerias estratégicas, pesquisas colaborativas e iniciativas de ensino, bem como na troca e produção de conhecimento. Em geral, a Internacionalização da Educação Superior se concentra na mobilidade de pessoal e estudantes, de modo a melhorar suas perspectivas internacionais e capacidades interculturais. No entanto, este artigo argumenta que, se as universidades querem ser verdadeiramente “internacionais”, elas devem começar “em casa”. Para tanto, faz-se necessário realizar uma revisão das atuais práticas de Internacionalização, envolvendo educadores, estudantes, desenvolvimento de pessoal, unidades de serviço profissional, e aqueles em posições de liderança, ajudando as instituições de Educação Superior a se orientarem em direção a valores básicos e abordagem ética para Internacionalização.